Senior activity rate, retirement incentives, and labor relations - Hélène Blake; Marc Sangnier (Kiel Institute for the World Economy (IfW), 2011)
In order to face the aging of their populations governments of developed countries reformed their retirement systems during the last two decades, by discouraging early retirement and increasing incentives to work for older workers. Senior participation rates to the labor force not only differ strikingly in level from one country to another, they also differ in their reaction to retirement incentives set by governments. This paper highlights how disutility to work can merely influence the effectiveness of such reforms. The authors build a highly stylized model according to which the reaction of senior activity rate to monetary incentives to work depends on the properties of the specific distribution of working conditions in the country. Second, taking the quality of labor relations as a proxy for working conditions, the authors show empirically that aggregate reactions to retirement incentives depend on the distribution of labor relations at country level. They use panel data for nineteen OECD countries from 1980 to 2004. They show that the elasticity of senior male labor force participation rate to retirement incentives is stronger in countries with better and more homogeneously distributed labor relations.
Keywords: J14; J26; Z10; 330; early retirement incentives; labor relations; senior activity rate